AKTIVITAS ANTIOKSIDAN EKSTRAK DAUN, PEDUNKULUS, DAN KULIT BUAH MUSA (AAA GROUP) âPISANG AMBON PUTIHâDENGAN METODE 2,2-DIFENIL-1-PIKRILHIDRAZIL (DPPH) DAN 2,2â-AZINO-BIS- 3-ETILBENZOTIAZOLIN-6-ASAM SULFONAT (ABTS) - Sefiany, Esther
Free radicals are atoms or groups of atoms that have one or more unpaired electrons so free radicals can cause disease for the body. Free radicals can be scavenged by using antioxidants, which potential source of antioxidant compounds have been found in several species of plants, one of them is banana. The objectives of this research were to study IC50 of leaves, peduncle, and peel from Musa (AAA group) „Pisang Ambon Putih?extracts using two methods of antioxidant testing which were DPPH and ABTS methods, total phenolic, flavonoid, and carotenoid content for each extract, analyze correlation of total phenolic, flavonoid, and carotenoid with IC50 of DPPH and ABTS methods, and the correlation of IC50 between the two testing methods DPPH and ABTS. Extraction was performed by reflux using gradient polarity solvent, namely n-hexane, ethyl acetate, and ethanol. Extracts were monitored by thin layer chromatography (TLC). IC50 of DPPH and ABTS scavenging activity, determination of total phenolic, flavonoid, and carotenoid content were performed by spectrophotometry UV-Vis, and their correlation with IC50 of DPPH and ABTS scavenging activity by Pearson?s method. The highest antioxidant activity was given by ethanolic peel extract of white ambon banana with the lowest IC50 of DPPH (0.39 ?g/mL) and the lowest IC50 of ABTS (0.36 ?g/mL). The ethanolic peel extract of white ambon banana had the highest total phenolics (29.28 g GAE/100 g), the ethyl acetate leaves extract of white ambon banana had the highest total flavonoids (13.00 g QE/100 g), and the ethyl acetate peel extract of white ambon banana had the highest total carotenoids (22.88 g BE/100 g). Total phenolics content in leaves and peduncle extracts of white ambon banana had high, negative, and significant correlation with IC50 of DPPH (r = -0,975; r = -0,979, p<0,01) and ABTS methods (r = -0,966; r = -0,985, p<0,01). Ethyl acetate and ethanol leaves, peduncle, and peel extracts of white ambon banana were very strong antioxidant by DPPH and ABTS methods. Phenolic compounds in leaves and peduncle extracts of white ambon banana were the major contributor in antioxidant activity using DPPH and ABTS methods. DPPH and ABTS assays gave linear result for all antioxidant activity of leaves, peduncle, and peel extracts of white ambon banana.